Pembuatan Bioetanol Dari Tandan Kosong Kelapa Sawit Dan Ubi Kayu - Nur Asma Deli; Hanifah Khairiah (Politeknik Kampar, 2024)
Renewable energy is energy that comes from renewable sources including geothermal, wind, bioenergy, sunlight, water flow and waterfalls as well as the movement and temperature differences of the ocean layers. One of the renewable energies that must continue to be developed is biomass energy derived from organic materials. The results of biomass conversion can be in the form of biogas, bioethanol, biodiesel, charcoal and so on. One of the alternative energies that can replace fossil energy sources is bioethanol. Raw materials that can be used as bioethanol are empty oil palm bunches and cassava. This study aims to determine whether the production of bioethanol from empty oil palm bunches and cassava produced is in accordance with Bioethanol Quality (SNI 7390-2012). This study consists of 5 processes, namely: preparation of raw materials, pretreatment of empty oil palm bunches, hydrolysis, fermentation, distillation. The final analysis results of bioethanol production with a density of 0.8896-0.911 gr/ml, brix content of 3-4%, pH level of 3-4, bioethanol yield of 15% - 30%. The optimum bioethanol yield is at 100% cassava variable with density data of 0.8896 gr/ml, brix content of 4%, pH level of 4, and yield of 30%. The results of the bioethanol quality test are not in accordance with the SNI 7390-2012 Standard.